Engineering the Conductive Network of Metal Oxide‐Based Sulfur Cathode toward Efficient and Longevous Lithium–Sulfur Batteries. Issue 41 (27th September 2020) - Wang, Jiayi; Li, Gaoran; Luo, Dan; Zhang, Yongguang; Zhao, Yan; Zhou, Guofu; Shui, Lingling; Wang, Xin; Chen, Zhongwei
Abstract: The rational design of sulfur cathode structure to suppress shuttling behaviors and expedite the conversion kinetics of polysulfides plays an essential role for the practical implementation of lithium–sulfur (Li–S) batteries. In this work, a unique consecutive and oxygen‐deficient niobium oxide (Nb2 O5− x ) framework featured with 3D ordered macroporous (3DOM) architecture and carbon nanotubes (CNTs) embedding is developed, which serves as a high‐performance sulfur immobilizer and catalytic promoter for polysulfide conversion. The 3DOM architecture affords a robust porous and open framework that favors electrolyte infiltration for fast ion/mass transfer, as well as interface exposure for massive host–guest interactions. More importantly, CNTs are designed as "antennae" embedded within the Nb2 O5− x skeleton, which not only contributes to a highly conductive framework but also intensifies the oxygen deficiency with enhanced sulfur immobilization and reaction catalyzation. Benefiting from these advanced features, Li–S cells based on S‐Nb2 O5− x /CNTs cathode achieve excellent cyclability with a high capacity retention of 847 mAh g −1 after 500 cycles and remarkable rate capability with 741 mAh g −1 at 5 C. Moreover, a high areal capacity of 6.07 mAh cm −2 can also be achieved under a high sulfur loading of 6 mg cm −2, illustrating great potential in the development of practical Li–S batteries. Abstract : A long‐range consecutive and oxygen‐deficient Nb2 O5− x /carbon nanotube (CNT) framework featuring a 3D ordered macroporous (3DOM) architecture and CNT embedding is developed and serves as an excellent lithium polysulfide adsorbent, as well as an efficient catalyst to promote sulfur conversion reaction kinetics. The 3DOM metal oxide with CNT embedding design holds great promise in the development of high‐performance Li–S batteries.